KEDEWASAAN MENIKAH PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Azwandi Azwandi (IAIN Bengkulu, 2018)
This study concludes that: 1) maturity according to Islamic law is marriage done within the boundary of a person has entered the baligh phase. Married adults are an attempt to minimize the problems that make the concept of sakinah, mawaddah and rahmah households will not be achieved. Households need to be built on the basis of maturity so as to cause psychological maturity of each partner either husband or wife. This maturity will generate thoughts, attitudes and behaviors that also mature in the household. Islamic Shari’a wants people who want to marry is really people who are ready mentally, physically and psy- chologically, mature and understand the meaning of a marriage that is part of worship. 2) married maturity according to Law No. 1 of 1974 is enacted in order to provide protection, justice and safeguard the human side of Indonesian society. Married maturity in Law No. 1 of 1974 aims to prevent the occurrence of marriage of children, so that young men who become hus- band and wife really have matured the soul of his body in forming a happy and eternal family. According to the Compilation of Islamic Law, the age limit of an independent or adult child is twenty-one years, as long as the child is not physically or mentally disabled or has never married